Crisis communication transformation through global digital news platforms - Rijkad Omar Dylian; Achmad Nurmandi; Muhammad Younus (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2025)
This study examines the shift of crisis communication in the digital era by examining the role of digital news platforms in shaping public engagement. The study uses a descriptive qualitative approach through analysis of 65 documents from scholarly sources and digital media, as well as social media tracking with NVivo 12 Plus and Tweetbinder. The case studies focused on the MCCC's response to COVID-19 in Indonesia and the Gaza crisis for global comparison. The results showed three main findings: (1) public engagement tends to be passive, indicated by the dominance of reposts (82%), reflecting information fatigue, low digital literacy, and distrust of institutions, (2) the distribution of public sentiment is dominated by neutral to negative tones (48-68% neutral, 25-38% negative), as a consequence of institutional communication strategies that use deny and diminish rather than rebuild approaches, (3) scientific discourse is still centered on institutional strategies and responses, without accommodating the complexity of local digital culture. As a practical recommendation, this study suggests a data-driven, participatory, and empathetic crisis communication model, as well as the integration of real-time sentiment monitoring and an actionable and forward-looking two-way feedback system.